2022
DOI: 10.1111/1753-6405.13252
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing refugees’ willingness to accept COVID‐19 vaccines in Greater Sydney: a qualitative study

Abstract: Objectives: Achieving high vaccination coverage is a critical strategy to reducing the spread of COVID‐19 infection. This study, undertaken before the Delta variant outbreak, aimed to understand potential drivers and barriers influencing COVID‐19 vaccine uptake for refugees. Methods: Four focus group interviews were conducted with 37 refugees from four language groups (Arabic, Dari, Dinka and Karen). Data were analysed thematically. Results: Willingness to accept COVID‐19 vaccines was associated with participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…Accordingly, they believed that GPs would have more opportunities to address COVID‐19 vaccine concerns than mass vaccination clinic staff. However, GPs may not always be easily accessible within an acceptable timeframe to the patient, 33 meaning some CALD individuals are turning to or relying on social media for their health/COVID‐19 information 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, they believed that GPs would have more opportunities to address COVID‐19 vaccine concerns than mass vaccination clinic staff. However, GPs may not always be easily accessible within an acceptable timeframe to the patient, 33 meaning some CALD individuals are turning to or relying on social media for their health/COVID‐19 information 9 …”
Section: Discussionmentioning
confidence: 99%
“…However, an online survey of refugees in Australia in mid‐2021 identified that 88% had not yet received a COVID‐19 vaccine 7 . Emerging evidence suggests that COVID‐19 vaccine hesitancy is prevalent among Australian CALD populations 8,9 . Focus groups conducted in mid‐2021 in New South Wales with CALD people indicated that 42% of participants were not planning to be vaccinated, and 29% were unsure or hesitant 8 .…”
Section: Introductionmentioning
confidence: 99%
“…2 The practical considerations of interacting in public life may have outweighed safety concerns for some participants. 29,30 Further, the emergence of new variants, increase in breakthrough infections, and waning immunity may have affected willingness to receive a booster vaccine and potentially generated concerns about effectiveness in the time since this study was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that information need, subjective norms, perceived risk, and information channels can affect COVID-19 vaccine willingness, but they did not ask participants explicitly about exposure to the concerning news. 12,21,22,24,25,29,30,[33][34][35][36] The effect of exposure to concerning news on willingness to receive a booster dose is an area that needs further research especially with the introduction of new vaccines. Our nding may be related to explicitly asking respondents about the news they had consumed in recent months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation